Leber’s Hereditary Optic Neuropathy. A Clinical Case - O. I. Karushin (Российский офтальмологический журнал, 2018)
Leber’s heredltary optic neuropathy (LHON) is a mitochondrial disease, which leads, in young age, to a gradual bilateral reduction of visual acuity unaccompanied by pain in the eyeballs. At present, no methods of effective prevention and treatment of LHON are known. The paper presents a clinical case of LHON in which visual functions improved following a revascularizing operation (optic nerve revascularization combined with therapeutic retrofilling of sclera) which used Alloplant biomaterial // Russian Ophthalmological Journal, 2016; 2: 84-9 . doi: 10.21516/2072-0076-2016-9-2-84-89 .